Long-term observation of hepatocellular carcinoma recurrence after liver transplantation at a European transplantation centre. Issue 6 (July 2019) - Foerster, Friedrich; Hoppe-Lotichius, Maria; Vollmar, Johanna; Marquardt, Jens U; Weinmann, Arndt; Wörns, Marcus-Alexander; Otto, Gerd; Zimmermann, Tim; Galle, Peter R
Background: The recurrence of hepatocellular carcinoma (HCC) is the strongest survival-limiting factor after liver transplantation (LT) in patients with HCC. In the face of donor organ shortage, it is necessary to identify factors associated with HCC recurrence in order to maximize the utility of the available grafts. Objective: To study the phenomenon of HCC recurrence after LT at a European transplantation centre over the past 20 years. Methods: Data from 304 HCC patients who underwent LT were prospectively recorded. Clinical and pathological factors were assessed for their association with recurrence. Results: Fifty-one patients (16.8%) had HCC recurrence after LT. Patients exceeding the Milan criteria developed HCC recurrence more frequently. The time point of recurrence did not affect survival after recurrence. Furthermore, there was no difference in survival between patients with intra- and extrahepatic recurrence. However, patients with recurrence due to needle tract seeding had a significantly better outcome than patients with other sites of recurrence. Conclusion: Our data support a restrictive use of patient selection criteria to help identify patients who have an increased risk of HCC recurrence after LT, and highlight the need to improve patient selection before LT in order to minimize the rate of HCC recurrence.